The impact of injury on match running performance following the return to competitive match-play over two consecutive seasons in elite European soccer players - Morgans, Ryland (2023)
Based on the assessment and diagnosis, the rest period following a moderate/severe injury may lead to de conditioning for the injured player and therefore an association with a prolonged rehabilitation, re-conditioning and return to sport is observed post-injury. The aim of the present study was to assess the impact of all injuries on match running performance following the return to competitive match-play over two consecutive seasons in elite European soccer players. A retrospective analysis was conducted utilizing data related to a player’s injury and match running performance. A club physiotherapist consistently recorded availability and injury data in a standardized format. Linear mixed modelling analysis revealed no difference between PRE and POST1, POST2, and POST3 for total distance, running distance, high-intensity distance, and sprint distance (all p >0.05). Although, maximum speed was significantly (p<0.05) lower in POST1 and POST2 when compared to PRE, in both cases with a large (ES = 1.88) effect. No significant difference was observed for maximum speed between PRE and POST3 (p=0.07). There were very low correlations between the number of days absent and changes in maximum speed between POST1 and PRE (r = 0.09, 95% CI -0.42 to 0.56), and POST2 and PRE (r = 0.10, 95% CI -0.42 to 0.57), respectively. In conclusion, no variation in distance variables were found regardless of one, two or three matches post-injury compared to pre-injury status. Moreover, maximum speed was lower during the first three matches post-injury, although the mean value was slightly lower. Finally, a low correlation between absent days and maximum speed loss between pre-injury and following one and two matches were found.